(untitled) (Medico Legal Update, 2021)
Protection of public interests in the bankruptcy process is regulated in the Indonesian Bankruptcy Law. However, the implementation of this provision raises problems both in the concept design of the public interest itself and in its protection mechanisms. The bankruptcy law provides at least three concepts of public interest, each of which can be identified with the interests of the wider community as creditors, the interest in the stability of the financial services sector, and the interests of state finances. The three concepts of public interest are protected with exclusive and prerogative powers on the regulators and supervisors as the authority of each field. Such protection mechanisms have so far only blocked the path of creditors and debtors, and provided immunity to special debtors, as the majority of authorities do not want to file bankruptcy requests and prefer to exercise their public powers.